Preparation method of narrow-band blue-light ZnSe / ZnS quantum dot material
By adding carboxylic acid ligands to the preparation process of ZnSe/ZnS quantum dot materials, the growth of quantum dots is limited, and the problem of preparation of narrow spectrum band blue light materials is solved, thereby achieving narrower emission spectrum bands and higher photoelectric properties.
Patent Information
- Application Number
- CN202411835141.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The prior art is difficult to prepare the narrow spectrum band blue light ZnSe/ZnS quantum dot material, resulting in a wide emission spectrum band and a high color rendering index cannot be achieved, affecting the performance of blue light devices.
By adding carboxylic acid ligand to the first precursor solution, the carboxylic acid ligand is used to bind to the quantum dot surface, limiting the excessive growth of the quantum dots, reducing the size distribution, and narrowing the emission band.
The preparation of narrow spectrum band blue light ZnSe/ZnS quantum dot material is realized, so that its luminous band is within the blue light range, and at the same time it has a smaller size distribution and a narrower emission spectrum band, which improves the photoelectric performance of quantum dots.
Smart Images

Figure CN119662257A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent materials, and in particular relates to a method for preparing a narrow-band blue light ZnSe / ZnS quantum dot material. Background Art
[0002] Light-emitting diodes (LEDs) have surpassed traditional lighting sources and are profoundly changing the lighting and display industries. Today, a variety of materials are available for commercial LEDs, such as III-V semiconductor LEDs, organic LEDs (OLEDs), and colloidal quantum dot LEDs (QLEDs). Blue light, the most energetic monochromatic light among the three primary colors, is also an important component for achieving white light illumination. Traditional blue-light-emitting LEDs are mostly based on III-V inorganic semiconductor epitaxial heterostructures, in which typical luminescent materials are GaN or InGaN. However, the harsh growth conditions and expensive equipment of such materials, as well as the limited luminescence spectrum of the materials, limit the widespread application of III-V semiconductor LEDs. Compared with III-V semiconductor LEDs, OLEDs have become an alternative in the field of LEDs due to their solution and vacuum deposition capabilities, large-area luminescence, and spectral control flexibility. However, the low thermal and chemical stability under high brightness and high current density conditions severely limits the application of OLEDs. QLEDs exhibit excellent high color rendering index (CRI), high stability, and high efficiency, showing great prospects among the new generation of electroluminescent materials. However, mature core-shell quantum dots still have many problems. Although the commonly used cadmium-based quantum dots can achieve three primary colors of light emission, their high unit price and the toxicity of heavy metal cadmium have limited their application prospects. Therefore, finding low-toxic or even non-toxic quantum dot electroluminescent materials is very important to promote the development of the lighting and display industries.
[0003] At present, quantum dots that do not contain heavy metals mainly include InP, ZnSe, CuInS2 and carbon-based quantum dots. Among them, CuInS2 and carbon-based quantum dots usually show a wider emission linewidth due to trap states or impurity emissions, and are therefore not suitable for display applications. In addition, the emission wavelength of CuInS2 quantum dots is mainly after 500nm, making it difficult to achieve blue light emission. The EQE of InP-based red and green QLEDs has reached 22.56% and 16.3% respectively, but the band gap of InP is relatively small (1.35eV), and it is also difficult to achieve pure blue light emission. At present, the maximum EOE of InP-based blue light devices at 492nm (cyan-blue) is only 2.8%. Overall, the development level of environmentally friendly blue light quantum dots lags behind that of red and green light materials, and further development is urgently needed.
[0004] As a direct bandgap semiconductor with a high bulk bandgap width (2.7 eV), ZnSe quantum dots are considered to be an environmentally friendly material with the potential to achieve efficient blue light emission, and it is easy to achieve blue-violet light emission. Therefore, it is still challenging to synthesize high-quality ZnSe quantum dots that emit narrow-band blue light in the 440-460nm band.
[0005] In recent years, the synthesis technology of ZnSe-based quantum dots has made great progress. At present, the quantum size effect has been used to achieve blue light emission by increasing the size of ZnSe quantum dots. However, it is currently impossible to achieve narrow-band emission, resulting in a wide band and an inability to achieve a high color rendering index, which greatly affects the performance of ZnSe blue light devices. Summary of the invention
[0006] The technical problem to be solved by the present invention is how to provide a method for preparing a narrow-band blue light ZnSe / ZnS quantum dot material so that its luminescent band is within the blue light range while having a smaller size distribution and a narrower emission band.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a narrow-band blue light ZnSe / ZnS quantum dot material comprises the following steps:
[0009] Step 1. Under a protective gas environment, prepare a zinc salt solution with a concentration of 0.2 to 0.5 mmol / mL, then add a first ligand to the zinc salt solution, heat to 120° C. under vacuum, and stir the reaction for 30 minutes until no bubbles are generated, to obtain a first precursor solution;
[0010] Step 2. Under a protective gas environment, prepare a second precursor solution with a concentration of 0.2 to 0.4 mmol / mL, a third precursor solution with a concentration of 1 to 2 mmol / mL, and a fourth precursor solution with a concentration of 1 to 3 mmol / mL;
[0011] Step 3. Under a protective gas environment, add a second ligand solution with a concentration of 0.2 to 1 mmol / mL to the first precursor solution, heat to 100 to 120° C. under vacuum, and stir to react for 20 to 40 minutes, wherein the volume ratio of the first precursor solution to the second ligand solution is 1:(2 to 4); then heat to 290 to 310° C., add the second precursor solution to the reaction solution, stir to react for 30 minutes, and nucleation is completed, wherein the volume ratio of the added second precursor solution to the first precursor solution is (10 to 20):1;
[0012] Step 4. In a protective gas environment, the first precursor solution and the third precursor solution are simultaneously injected into the reaction solution obtained in step 3, and 0.1-0.3 mL of the first ligand is injected every 20 min to perform epitaxial growth, wherein the injection rate of the first precursor solution is 0.5-1 mL / h, and the injection rate of the third precursor solution is 0.1-0.2 mL / h; during the injection process, the reaction liquid is extracted, and the position of the luminescent center is observed using a fluorescence spectrophotometer. When the luminescent center reaches ~460 nm, the injection is stopped, and the reaction is kept warm for 30 min;
[0013] Step 5. Under a protective gas environment, inject the first precursor solution and the fourth precursor solution into the reaction solution obtained in step 4 at the same time to carry out shell growth, wherein the injection rate of the first precursor solution is 0.5-1 mL / h, and the injection rate of the fourth precursor solution is 0.1-0.2 mL / h; after continuous injection for 1 hour, stop the injection, react for 30 minutes, naturally cool to room temperature, separate, and obtain ZnSe / ZnS quantum dots.
[0014] Furthermore, the solute of the zinc salt solution in step 1 is zinc salt, and the solvent is trioctylamine, octadecene or liquid paraffin.
[0015] Furthermore, in step 1, the first ligand is a carboxylic acid ligand, and the general chemical formula is CH3-[CH2] n -COOH, n≥8 or C n H (2n-2) O2, n≥10; the molar ratio of the first ligand to the Zn ion is (3-6):1.
[0016] Furthermore, in step 2, the solute of the second precursor solution is selenium powder, and the solvent is diphenylphosphine (C6H5)2PH; the solute of the third precursor solution is selenium powder, and the solvent is trioctylphosphine C 24 H 51 P; the solute of the fourth precursor solution is sulfur powder, and the solvent is trioctylphosphine C 24 H 51 P.
[0017] Furthermore, in step 3, the solute of the second ligand solution is a primary amine, and the chemical formula is CH3-[CH2] m -NH2, m≥10; the solvent is trioctylamine, octadecene or liquid paraffin.
[0018] Furthermore, the luminescence peak half-width of the ZnSe / ZnS quantum dots obtained in step 5 is less than 12 nm.
[0019] Furthermore, the separation in step 5 is centrifugal separation, and the rotation speed of the centrifugal separation is 6000-8000 rpm.
[0020] Furthermore, the protective gas is one of nitrogen, helium, argon and neon.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention provides a method for preparing a narrow-band blue light ZnSe / ZnS quantum dot material, which adds a carboxylic acid ligand to a first precursor solution and utilizes the carboxylic acid ligand to bind to the surface of the quantum dots to limit the excessive growth of the quantum dots, thereby reducing the size distribution of the quantum dots and narrowing the emission band of the quantum dots.
[0023] 2. The present invention provides a method for preparing a narrow-band blue light ZnSe / ZnS quantum dot material. Carboxylic acid is added during the epitaxial growth process. While reducing the size distribution of quantum dots, the surface defects of the material can be further modified to inhibit energy quenching caused by defects and improve the photoelectric performance of quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a transmission electron microscope image of the ZnSe / ZnS quantum dot luminescent material obtained in the example;
[0025] Figure 2 The photoluminescence spectrum of the ZnSe / ZnS quantum dot luminescent material obtained in the example;
[0026] Figure 3 This is a transmission electron microscope image of the ZnSe / ZnS quantum dot luminescent material obtained in the comparative example;
[0027] Figure 4 The photoluminescence spectrum of the ZnSe / ZnS quantum dot luminescent material obtained in the comparative example. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0029] Example
[0030] A method for preparing a narrow-band blue light ZnSe / ZnS quantum dot material comprises the following steps:
[0031] Step 1. Prepare a 100 mL three-necked flask, clean it with deionized water and ethanol, blow it dry, and put a clean magnet in it; weigh 3.668 g of Zn(CH3COO)2 into the three-necked flask, add 10 mL of trioctylamine as a solvent and 30 mmol of oleic acid as a ligand, and heat to 120 ° C under vacuum, stir and react for 30 min until no bubbles are generated, and obtain the first precursor solution;
[0032] Step 2. In an inert gas atmosphere, add 39.5 mg of selenium powder and 1 mL of diphenylphosphine, 789.6 mg of selenium powder and 10 mL of trioctylphosphine, and 320.6 mg of sulfur powder and 10 mL of trioctylphosphine to three sample bottles, respectively, seal them, and disperse them by ultrasonic vibration until they are clear, to obtain the second, third, and fourth precursor solutions;
[0033] Step 3. Take 0.4 mL of the prepared first precursor solution and inject it into a 100 mL three-necked flask, and inject 5 mL of 0.2 mmol / mL oleylamine solution (solvent is trioctylamine), heat to 120 ° C under vacuum, stir and react for 30 minutes until it becomes clear, then heat to 300 ° C, quickly inject 0.4 mL of the second precursor solution into the reaction solution, maintain the temperature for 30 minutes, and nucleation is completed;
[0034] Step 4. Inject the first precursor solution and the third precursor solution into the reaction solution obtained in step 3 at the same time, and inject 0.3 mL of oleic acid every 20 minutes to perform homoepitaxial growth, wherein the injection rate of the first precursor solution is 0.6 mL / h, and the injection rate of the third precursor solution is 0.2 mL / h; extract the reaction liquid during the injection process, and use a fluorescence spectrophotometer to observe the position of its luminescence center. When the luminescence center reaches ~460 nm, stop the injection and keep the reaction warm for 30 minutes;
[0035] Step 5. Inject the first precursor solution and the fourth precursor solution into the reaction solution obtained in step 4 at the same time to perform shell growth, wherein the injection rate of the first precursor solution is 0.6 mL / h, and the injection rate of the fourth precursor solution is 0.2 mL / h; after continuous injection for 1 hour, stop the injection, react for 30 minutes, and naturally cool to room temperature; take 4 mL of the cooled stock solution and place it in a centrifuge tube, add one volume of n-hexane and three volumes of anhydrous ethanol, fully shake and centrifuge at a speed of 8000 rpm for 5 minutes, then redisperse the precipitate obtained after centrifugation in 2 mL of n-hexane solvent and add 4 mL of anhydrous ethanol, shake fully, centrifuge again at the same speed for 5 minutes, and disperse the precipitate in 1 mL of n-hexane. Finally, filter the resulting solution through a 0.22-micron filter head and put it into a clean glass bottle and seal it for storage. The ZnSe / ZnS quantum dot luminescent material has a transmission electron microscope image as shown in FIG. Figure 1 shown.
[0036] Comparative Example
[0037] The difference between the comparative example and the embodiment is that: in step 4, during the homoepitaxial growth process, oleic acid is not injected; the remaining steps are exactly the same as those of the embodiment.
[0038] The luminescent materials obtained in the embodiment and the comparative example were tested for photoluminescence spectra, and the results are as follows: Figure 2 and4 Its PL peak wavelength and PL peak half-width are shown in Table 1.
[0039] Table 1
[0040] PL peak wavelength (nm) PL peak half-width (nm) Example 450 11.3 Comparative Example 452 21.3
[0041] It can be seen from Table 1 and the attached figure that the half-height width of the photoluminescence peak of the material can be significantly reduced by adding carboxylic acid ligands. This is because under the action of excessive carboxylic acid, the surface of the quantum dots is combined, the growth of large-particle quantum dots is inhibited, and the small-sized quantum dots continue to grow, and the size distribution of the material is reduced, thereby causing the narrowing of the luminescence spectrum.
[0042] The present invention has been described by the above embodiments, but it should be understood that the above embodiments are only for the purpose of example and description, and are not intended to limit the present invention to the scope of the described embodiments. In addition, it can be understood by those skilled in the art that the present invention is not limited to the above embodiments, and more variations and modifications can be made according to the teachings of the present invention, and these variations and modifications all fall within the scope of the protection claimed by the present invention. The protection scope of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing narrow-band blue light ZnSe / ZnS quantum dot material, characterized in that: The following steps are involved: Step 1. Under a protective gas environment, prepare a zinc salt solution with a concentration of 0.2 to 0.5 mmol / mL, then add a first ligand to the zinc salt solution, heat to 120° C. under vacuum, and stir until no bubbles are generated to obtain a first precursor solution; Step 2. Under a protective gas environment, prepare a second precursor solution with a concentration of 0.2 to 0.4 mmol / mL, a third precursor solution with a concentration of 1 to 2 mmol / mL, and a fourth precursor solution with a concentration of 1 to 3 mmol / mL; Step 3. Under a protective gas environment, add a second ligand solution with a concentration of 0.2 to 1 mmol / mL to the first precursor solution, heat to 100 to 120° C. under vacuum, and stir to react for 20 to 40 minutes, wherein the volume ratio of the first precursor solution to the second ligand solution is 1:(2 to 4); then heat to 290 to 310° C., add the second precursor solution to the reaction solution, stir to react for 30 minutes, and nucleation is completed, wherein the volume ratio of the added second precursor solution to the first precursor solution is (10 to 20):1; Step 4. In a protective gas environment, the first precursor solution and the third precursor solution are simultaneously injected into the reaction solution obtained in step 3, and 0.1-0.3 mL of the first ligand is injected every 20 min to perform epitaxial growth, wherein the injection rate of the first precursor solution is 0.5-1 mL / h, and the injection rate of the third precursor solution is 0.1-0.2 mL / h; during the injection process, the reaction liquid is extracted and the position of the luminescent center is tested. When the luminescent center reaches 460 nm, the injection is stopped and the reaction is kept warm for 30 min; Step 5. Under a protective gas environment, inject the first precursor solution and the fourth precursor solution into the reaction solution obtained in step 4 at the same time to carry out shell growth, wherein the injection rate of the first precursor solution is 0.5-1 mL / h, and the injection rate of the fourth precursor solution is 0.1-0.2 mL / h; after continuous injection for 1 hour, stop the injection, react for 30 minutes, naturally cool to room temperature, separate, and obtain ZnSe / ZnS quantum dots.
2. The method for preparing narrow-band blue light ZnSe / ZnS quantum dot material according to claim 1, characterized in that: The solute of the zinc salt solution in step 1 is zinc salt, and the solvent is trioctylamine, octadecene or liquid paraffin.
3. The method for preparing narrow-band blue light ZnSe / ZnS quantum dot material according to claim 1, characterized in that: Step 1: The first ligand is a carboxylic acid ligand, and the general chemical formula is CH3-[CH2] n -COOH, n≥8 or C n H (2n-2) O2, n≥10; the molar ratio of the first ligand to the Zn ion is (3-6):
1.
4. The method for preparing narrow-band blue light ZnSe / ZnS quantum dot material according to claim 1, characterized in that: Step 2: The solute of the second precursor solution is selenium powder, and the solvent is diphenylphosphine (C6H5)2PH; the solute of the third precursor solution is selenium powder, and the solvent is trioctylphosphine C 24 H 51 P; the solute of the fourth precursor solution is sulfur powder, and the solvent is trioctylphosphine C 24 H 51 P.
5. The method for preparing narrow-band blue light ZnSe / ZnS quantum dot material according to claim 1, characterized in that: Step 3: The solute of the second ligand solution is a primary amine, and the chemical formula is CH3-[CH2] m -NH2, m≥10; the solvent is trioctylamine, octadecene or liquid paraffin.
6. The method for preparing narrow-band blue light ZnSe / ZnS quantum dot material according to claim 1, characterized in that: The luminescence peak half-width of the ZnSe / ZnS quantum dots obtained in step 5 is less than 12 nm.
7. The method for preparing narrow-band blue light ZnSe / ZnS quantum dot material according to claim 1, characterized in that: The separation in step 5 is centrifugal separation, and the rotation speed of the centrifugal separation is 6000-8000rpm.
8. The method for preparing narrow-band blue light ZnSe / ZnS quantum dot material according to claim 1, characterized in that: The protective gas is one of nitrogen, helium, argon and neon.
Citation Information
Patent Citations
Blue light cadmium-free quantum dot, preparation method thereof and quantum dot photoelectric device
CN111849483A
Blue light InP / ZnSe / ZnS core-shell quantum dot and preparation method thereof
CN117363359A
LED device, light guide plate and backlight module
US20160146999A1
Preparation method of znse quantum dot, znse quantum dot, znse structure, and display device
WO2022134044A1